ORGANIZING THE WORK OF THE DONOR BREAST MILK BANK AT THE LVIV PERINATAL CENTER IS AN EXPERIENCE THAT MOTIVATES FURTHER DEVELOPMENT - М. Малачинська; М. Кісельова; О. Шлемкевич; Н. Вереснюк; Г. Коваленко (Неонатологія, хірургія та перинатальна медицина, 2025)
Human milk is considered the primary source of nutrition for breastfed infants and is justifiably regarded as the “gold standard.” Errors in feeding breastfed infants negatively affect not only the child’s physical health but also their functional capacities. No substitute for human milk can compete with the presence of biologically active substances inherent to the mother-child symbiosis.